2000
DOI: 10.1038/labinvest.3780053
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cell-Mediated Cytotoxicity Toward Thyrocytes: The Importance of Fas/Fas Ligand Interaction Inducing Apoptosis of Thyrocytes and the Inhibitory Effect of Thyroid-Stimulating Hormone

Abstract: SUMMARY:The accumulation of activated CD4 ϩ T cells and antigen (Ag)-dependent cellular interactions between thyrocytes and CD4 ϩ T cells have been determined in thyroid gland from patients with Graves' disease. The Fas/Fas ligand (FasL) interaction between antigen-presenting cells and T cells regulates the apoptosis of the former cells triggered by the latter cells. The inhibition of Fas-mediated apoptosis in thyrocytes could be a underlying mechanism of hyperplasia of thyrocytes in patients with Graves' dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Fas was also upregulated in the thyrocytes of patients with Graves' disease (Sera et al, 2000). The thyroid gland of Graves' disease patients contains TUNEL-positive thyrocytes and PCNA-positive thyrocytes, together with monocuclear cell infiltration (Sera et al, 2000). These data suggest that apoptosis and proliferation of thyrocytes may be abnormally accelerated, however, the proliferation of thyrocytes may outweigh their apoptosis, resulting in hyperplasia.…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 82%
See 3 more Smart Citations
“…Fas was also upregulated in the thyrocytes of patients with Graves' disease (Sera et al, 2000). The thyroid gland of Graves' disease patients contains TUNEL-positive thyrocytes and PCNA-positive thyrocytes, together with monocuclear cell infiltration (Sera et al, 2000). These data suggest that apoptosis and proliferation of thyrocytes may be abnormally accelerated, however, the proliferation of thyrocytes may outweigh their apoptosis, resulting in hyperplasia.…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 82%
“…Giordano et al (1997) reported the constitutive expression of FasL (Fas ligand) on normal and Hashimoto's thyroiditis (HT) thyrocytes using immunohistochemistry, flow cytometry, and RT-PCR. The percentage of FasL-positive thyrocytes in Graves' thyroid was less than in normal thyroids (Sera et al, 2000). In contrast, another study was unable to detect FasL in thyrocytes (Xerri et al, 1997).…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 85%
See 2 more Smart Citations
“…Various cytokines modulate hormone production by binding to specific receptors in endocrine tissues and vice versa, hormones bind to their own receptors on immune cells and are able to influence their function (27)(28)(29)(30). TSH has been shown to induce direct T cell, B cell and dendritic cell activation and the release of proinflammatory cytokines, leading to an inflammatory state that affects not only the thyroid gland, but other tissues as well, including the skin (28)(29)(30)(31)(32). This effect is amplified in the setting of autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 99%